PENERAPAN MODEL SELF DIRECTED LEARNING DALAM PEMBELAJARAN MENULIS TEKS PUISI BERDASARKAN UNSUR PEMBANGUN PADA PESERTA DIDIK KELAS X SMAN 9 BANDUNG TAHUN PELAJARAN 2022/2023 - Irma Herawati; Titin Nurhayatin; Musaddad Abdul Azis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low ability of students to write. This is caused by the lack of variety of learning models used by educators. The use of varied, creative and innovative learning models can make students more active and motivated during learning activities. One of the learning models that can be used is the self-directed learning model. The purpose of this research was to test the writer's ability to plan, implement, and assess learning to write poetry using the self-directed learning model, to test the ability of class X students at SMAN 9 Bandung in writing poetry, to test the effectiveness of the self-directed learning model in learning to write poetry , as well as to determine differences in writing ability between the experimental class using the self-directed learning model and the control class using the question and answer method. The research method used is a quantitative method with the type of quasi-experimental research using literature review, trial and error, observation, and test techniques. The data obtained were in the form of students' pretest and posttest from both the experimental class and the control class. The results of this study: 1) The author is able to plan, implement, and evaluate learning to write poetry using the self-directed learning model with an average planning score of 3.7 and an implementation value of 3.9. 2) The ability of students in writing poetry has increased with an average pretest score of 55.4 to a posttest with an average score of 82,9. 3) The self-directed learning model is effectively used in learning to write poetry. This is evidenced by the results of the Mann-Whitney test with sig. 0.000 <0.05 there is a significant difference between the experimental class and the control class. Based on the explanation above, the self-directed learning model is effectively used in learning to write poetry.